2012
DOI: 10.1002/er.2952
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis and optimization of a building cooling heating power system driven by solar energy based on organic working fluid

Abstract: SUMMARY Building cooling heating power (BCHP) systems as a kind of distributed energy resource have shown a great potential in improving energy efficiency and meeting multiple energy demands in buildings. In this paper, we present a BCHP system driven by solar energy with flat‐plate solar collectors. A modified system efficiency is introduced to evaluate the whole day performance of the system more accurately. Based on the mathematical models and simulation platform established, we have investigated the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The simplest way of regaining the wasted energy is to utilise it for heating. To this end, a mature technology known as ‘combined heat and power’, is an effective power supply method to achieve energy savings and cost reduction as well as greenhouse gas emission mitigation . As mentioned in , £176 million annual cost reduction on the energy production and the mitigation of 2.1 million tons of CO 2 emission were achieved following the installation of 1 million micro‐CHP units in the UK.…”
Section: Tri‐generation and Poly‐generation Systemsmentioning
confidence: 99%
“…The simplest way of regaining the wasted energy is to utilise it for heating. To this end, a mature technology known as ‘combined heat and power’, is an effective power supply method to achieve energy savings and cost reduction as well as greenhouse gas emission mitigation . As mentioned in , £176 million annual cost reduction on the energy production and the mitigation of 2.1 million tons of CO 2 emission were achieved following the installation of 1 million micro‐CHP units in the UK.…”
Section: Tri‐generation and Poly‐generation Systemsmentioning
confidence: 99%
“…They found the maximum energy efficiency to be 57% and the maximum exergy efficiency to be 36%. Wang et al studied a system for heating, cooling, and power production, which is driven by flat plate collectors, which include an ORC with ejector device. They found that the system energy efficiency is 27.24% in the cooling‐power mode, 19.10% in the heating‐power mode, and only 10.47% in the power mode.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the maximum power generation of this system is in the power mode and CHP mode. Wang et al [22] examined an energy optimization of a flat plate solar collector with an ORC for the combined generation of cooling, heating, and power (multigeneration system). NSGA-II algorithm was applied to optimize the total heat transfer area and the power production.…”
Section: Introductionmentioning
confidence: 99%
“…For the CCP and CHP modes, the optimum average output was 5.84, 8.89 kW, respectively. 3 Wang et al [22] Solar powered triple cycle to produce electrical power, heating, and cooling…”
Section: Introductionmentioning
confidence: 99%